COVID-19 Age-Mortality Curves for 2020 Are Flatter in Developing Countries Using Both Official Death Counts and Excess Deaths - Demombynes, Gabriel (World Bank, Washington, DC, 2021)
Using official COVID-19 death counts for 64 countries and excess death estimates for 41 countries, this paper finds a higher share of pandemic-related deaths in 2020 were at younger ages in middle-income countries compared to high-income countries. People under age 65 constituted on average (1) 11 percent of both official deaths and excess deaths in high-income countries, (2) 40 percent of official deaths and 37 percent of excess deaths in upper-middle-income countries, and (3) 54 percent of official deaths in lower-middle-income countries. These contrasting profiles are due only in part to differences in population age structure. Both COVID-19 and excess death age-mortality curves are flatter in countries with lower incomes. This is a result of some combination of variation in age patterns of infection rates and infection fatality rates. In countries with very low death rates, excess mortality is substantially negative at older ages, suggesting that pandemic-related precautions have lowered non-COVID-19 deaths. Additionally, the United States has a younger distribution of deaths than countries with similar levels of income.